P0661DIAGNOSTIC VALUE OF FULL AGE SPECTRUM EQUATION AS A PREDICTOR OF MORPHOLOGICAL LESIONS IN PATIENTS WITH GLOMERULONEPHRITIS. (6th June 2020) - Elena, Saganova; Galkina, Olga; Sipovskii, Vasiliy; Kayukov, Ivan; Smirnov, Alexei
Abstract: Background and Aims: Glomerular filtration rate (GFR) is generally accepted as a best overall index of kidney function. However, it remains controversial to choose the optimal equation to estimate GFR in patients with glomerulonephritis (GN). Recent studies have reported that newly developed full age spectrum equation based on normalized serum creatinine (FASsCr) showed improved validity and was less biased, more accurate than currently recommended sCr-based eGFR equations. Our aim was to assess FASsCr equation as a predictor of various morphological lesions in patients with GN. Method: 100 patients [48 female, age Me 39 (27; 54) years] with biopsy proven primary GN and without acute kidney injury, infectious diseases, severe heart failure, respiratory insufficiency, cancer were included in the study. Minimal change disease was diagnosed in 9% of cases based on the results of kidney biopsy, in 28% – focal segmental glomerulosclerosis, in 26% – membranous nephropathy and in 37% – IgA-nephropathy. Serum creatinine (sCr) level was measured by enzymatic method (Uni Cel DxC 800 PRO, «Beckman Coulter», USA). eGFR was calculated using FASsCr equation. The extent of global glomerulosclerosis (GS) was assessed quantitatively as a sum of full and focal sclerotic glomeruli. Tubulo-interstitial fibrosis (TIF) and tubular atrophy (TA) were assessed semi-quantitatively (0-lesions absent; 1-mild focal tubular and interstitial lesions; 2-moderate tubular and interstitial lesions; 3 - diffuse tubular and interstitial lesions). All patients consistently were separated into 2 groups according to the degree of each morphological lesion (GS, TIF or TA): "mild" (GS<25% or TIF/TA grade 0 or 1) and "severe" (GS ≥ than 25% or TIF/TA grade 2-3). Results: eGFR using FASsCr equation positively correlated (p<0, 001 in all cases) with GS (r=0, 44), TIF (r=0, 64) and TA (r=0, 61) and was significantly higher in patients with "mild" GS, TIF and TA (p<0, 001) in comparison with "severe" group. Using ROC-analysis all patients were separated (p<0.001) in 2 groups using FASsCr equation according to the degree of morphological lesions ("mild" or "severe"): GS (Sn – 48.8%, Sp – 88.1%, ACC – 72.0%, AUC – 0.696, cut-off value – 47 ml/min/1.73m 2), TIF (Sn - 75.4%, Sp – 76.9%, ACC – 76.0%, AUC – 0.815, cut-off value – 72 ml/min/1.73m 2), TA (Sn – 65.9%, Sp – 88.8%, ACC – 70.0%, AUC – 0.798, cut-off value – 74 ml/min/1.73m 2), (Figure). Conclusion: Our results show that FASsCr equation is a significant marker of various morphological lesions in patients with GN. FASsCr equation predominantly can be used as a predictor of mild degree of interstitial sclerosis and tubular atrophy with high diagnostic value. Figure: ROC curves with 95% CI of BM panel for A – GS; B – TIF; C – TA